2015
DOI: 10.1021/acs.biochem.5b00111
|View full text |Cite
|
Sign up to set email alerts
|

Mutants of Metal Binding Site M1 in APP E2 Show Metal Specific Differences in Binding of Heparin but Not of sorLA

Abstract: The amyloid precursor protein (APP) and its neurotoxic cleavage product Aβ are key players in the development of Alzheimer's disease (AD) and appear to be essential for neuronal development and cell homeostasis. Proteolytic processing of APP and its physiological function depend on its interaction with heparin and are influenced by the binding of metal ions and sorLA. We created various mutations of metal binding site M1 residing within the extracellular E2 domain of APP. Using isothermal titration calorimetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 51 publications
(126 reference statements)
1
15
0
Order By: Relevance
“…[32][33][34][35] Metal binding to the M1 site enhances the binding affinity of APP E2 for heparin. 36 These previous observations may help to understand the specificity of APP E2 in forming stable Cu(I)-mediated ternary complexes with the Cu(I) probe ligands that can be disrupted by heparin. Each ligand (Fig.…”
Section: Nature Of the App E2 Ternary Complexes And Their Biological mentioning
confidence: 88%
See 2 more Smart Citations
“…[32][33][34][35] Metal binding to the M1 site enhances the binding affinity of APP E2 for heparin. 36 These previous observations may help to understand the specificity of APP E2 in forming stable Cu(I)-mediated ternary complexes with the Cu(I) probe ligands that can be disrupted by heparin. Each ligand (Fig.…”
Section: Nature Of the App E2 Ternary Complexes And Their Biological mentioning
confidence: 88%
“…25 A further mutation study demonstrated that stable binding of Cu(II) by the M1 site requires coordination by all four His ligands, but only a sub-set of 2-3 for Zn(II). 36 As heparin itself shows no detectable affinity for Cu(I), it is unlikely that the glycosaminoglycan is directly involved in the Cu(I) binding.…”
Section: App E2 Distorts the Solution Spectra Of [Cu I L 2 ] 3àmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, copper and zinc binding to APP/APLPs has been shown to alter their cis-and trans-directed dimerization properties. Zinc binding to the E2 domain increases the affinity of APP to heparin (Multhaup et al 1995;Dienemann et al 2015) and favors oligomerization of E2 domains from APP and APLP1 but not from APLP2 (Mayer et al 2014). Nevertheless, zinc-mediated oligomerization in the cellular context has been observed for all APP family members and is most pronounced for APLP1 (Mayer et al 2014(Mayer et al , 2016.…”
mentioning
confidence: 99%
“…; Dienemann et al . ) and favors oligomerization of E2 domains from APP and APLP1 but not from APLP2 (Mayer et al . ).…”
mentioning
confidence: 99%